The Concept of Dhikr in the Quran and its Relation to Mental health (Analysis Study of Surah Ar-Ra'd Verse 28) - Izzan, Ahmad; Tamimi, Tatang Muslim (UIN Sunan Gunung Djati Bandung, 2022)
Islam is very concerned about human beings, namely that they must live healthy lives in overall health situations and conditions, physically, mentally, spiritually, and socially. Mental health is key to a person's success in achieving a goal. If mentally ill, the continuation will find it challenging to get the purpose of his life. With a lot of dhikr either through the heart or verbally, or by both the heart and the tongue, you will get an inner experience that other people may not be able to get. Dhikr will open the veil in the hearts of people who in their lives only think about material things. Therefore, the author would like to reveal in this study that the concept of dhikr in the Koran is related to mental health in Q.S.Ar-Ra'd (13): 28. The Library Research method used in this research is through Content Analysis. In this study the author will use the Book of Tafsir Al-Azhar, the Book of Tafsir Al-Misbah, and the Book of Tafsir Al-Maraghi. As a reference book in this research. The analysis results of the word dhikr can be concluded, namely dhikr with the heart and continuously, for believers, it will thrill their hearts. Because they are afraid of Allah's punishment, leading to calm, serenity, and peace. So the result is a correlation between dhikr and mental health.